GENDER APPROACH IN THE ANALYSIS OF EMPLOYEE LOYALTY DETERMINANTS AT PRAMANA EXPERIENCE HOTELS & RESORTS IN BALI - Ni Made Yuami Damayanti; Putu Yudy Wijaya; I Komang Gede (CAPITAL: Jurnal Ekonomi dan Manajemen, 2025)
The aim of this research is to investigate the impact of Gender Approach in the Determination of Employee Loyalty at the Pramana Experience Hotels & Resorts in Bali. Gender is measured using dummy variables. This study also identifies the role of Gender as a moderating variable in the relationship between workplace spirituality, work-family conflict, and subjective wellbeing on Employee Loyalty. The analysis method used is PLS-SEM. Data were collected through an online Google Form questionnaire, with a total of 131 female employee respondents. The results reveal that only workplace spirituality and work-family conflict have a significant impact on subjective well-being. Workplace spirituality, work-family conflict, and subjective well-being significantly affect employee loyalty. Furthermore, evidence was found that gender statistically does not have an impact on Employee Loyalty. The indirect relationship testing reveals that subjective well-being is able to mediate the relationship between workplace spirituality and work-family conflict on employee loyalty. Based on these findings, it is concluded that gender status does not have a significant impact on employee loyalty.